Palm stem anatomy and computer-aided identification: The Coryphoideae (Arecaceae) - Thomas, Romain; De Franceschi, Dario (American journal of botany, 2013)
• Premise of the study: Through a comparative study of the anatomy of palm stems and the development of an interactive web-based tool, the present paper aims to provide a method of identifying palm stems. The stem determination will allow specialists in archaeology and paleontology to better exploit palm fossils for paleoenvironmental interpretations. The precise anatomical description also provides new systematic data tested in phylogenetic analyses (new anatomical characters, stratigraphic calibrations).• Methods: Stem samples were collected, including representatives from each tribe of the five palm subfamilies, and 25 descriptors (with 78 states) were defined within 37 taxa and registered in Xper2, a management tool for taxonomic description that allows editing of standardized descriptions. Some descriptors were used for the first time in this work; others were compiled from the existing literature. While all the palm subfamilies were included in the present study, the focus here is on the Coryphoideae.• Key results: Descriptors were mainly based on the general organization of the transverse section and the structure of the fibrovascular bundles as well as ground parenchyma. Coryphoideae have 1, 2, or more metaxylem elements, whereas the other subfamilies systematically present only 1 or 1 and 2 metaxylem elements. The centrifugal differentiation of the sheath of phloem fibers is described in other subfamilies but is not found in the Coryphoideae (except in Caryoteae).• Conclusion: Some tribes are easy to identify (Borasseae, Cryosophileae, Phoeniceae, Caryoteae); others are rather heterogeneous and more difficult to define (Chuniophoeniceae, Trachycarpeae). Caryoteae presents some unique states of the Arecoideae.